Basewide Energy Systems Plan for Fort McPherson, Georgia, Addressing Increments A, B, and G, Volume 1. Executive Summary - JRB ASSOCIATES INC MCLEAN VA (1981)
This report presents the results of Increments A, B, and G of the Energy Engineering Analysis Survey conducted at Fort McPherson in Atlanta, Georgia, by JRB Associates under Contract No. DACA21-8O-C-OO14. The report includes analyses of the energy patterns at the Post, and the identification and evaluation of energy conservation opportunities. The results obtained indicate tha energy use at Fort McPherson can potentially be reduced by 28 percent by FY 1985, compared to the FY 1975 energy use. Initial data for the study were gathered through a series of site visits during which buildings were inventoried, patterns of building energy use were identified, and typical buildings were selected for detailed study in each category. The energy use data were analyzed to determine how much energy the various types of buildings use and the functional energy use. Figures 1, 2, and 3 provide a summary of the building inventory and energy use. Fuel oil, natural gas, and electricity are the main energy sources at Fort McPherson. A summary of FY 1979 basewide energy use by fuel type is given in Figure 4, which shows that electricity accounts for approximately 56 percent of total energy use. Total energy use at the Base for the last 3 years is shown in Table 1. A detailed study was performed of the usage of all energy sources, including an analysis of monthly consumption figures. Peak demands for both fuel oil and natural gas occurred in the winter months due to space heating requirements. The electrical peak demand was in the summer months to satisfy air conditioning requirements. The end-uses of fuel oil and natural gas are shown in Figure 5, while the end-uses of electricity are shown in Figure 6. Table 2 shows the current energy use at Fort McPherson by building category and system.